Performance analysis of multiprocessor DSPs a stream-oriented component model. - Thiele, L. (IEEE Signal processing magazine)
This article introduces a composable component model that can be used for performance analysis of complex digital signal processing (DSP) systems consisting of several computation resources communicating via some shared media. It reviews different methods of analyzing the performance of such communication-centric systems, including simulation, trace-based simulation, and symbolic methods. Finally, a component model that can be used to formally state the relationship between the usage and the processing capabilities of different computation and communication resources is established.